Alternol Sensitizes Renal Carcinoma Cells to TRAIL-Induced Apoptosis - Ren, Yu; Wang, Xue; Huang, Shuaishuai; Xu, Yangkai; Weng, Guobin; Yu, Rui (Frontiers in Pharmacology, 2021)
Purpose: Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) is a promising anticancer agent with the ability to selectively induce cell death in cancer cells while sparing normal cells. However, the application of TRAIL-based anti-tumour therapies has been hindered by drug resistance. Alternol, a novel compound that can be purified from microbial fermentation, possesses anti-tumour activity in various cancers. In this study, we found that alternol was able to sensitize TRAIL-resistant renal carcinoma cells to TRAIL-induced apoptosis. Materials and methods: Cytotoxic activity was measured by MTT assay. Apoptotic rate was evaluated using PI/Annexin V assay. Changes of protein and mRNA were investigated by western blot and real-time PCR. Luciferase assay analyzed whether CHOP transcriptionally controlled DR5 expression. Tumour xenograft model tested anti-tumor effects of alternol/TRAIL in vivo. Results: When the mechanisms were investigated, we found that alternol up-regulated death receptor (DR) 5 levels. Silencing DR5 by RNA interference abrogated the sensitizing effect of alternol on TRAIL-mediated apoptosis. Moreover, alternol decreased the expression of anti-apoptotic proteins while increasing the expression of pro-apoptotic proteins. In addition, alternol up-regulated CHOP expression, which is required for the sensitizing effect of alternol on TRAIL-induced apoptosis since silencing CHOP abolished the synergistic effect. We also observed that alternol-induced DR5 up-regulation was dependent on reactive oxygen species (ROS) production. Removing ROS inhibited DR5 induction and suppressed the anti-apoptotic proteins induced by alternol. Conclusions: Taken together, our results indicate that alternol potentiates TRAIL-mediated apoptosis through inhibiting anti-apoptotic proteins and up-regulating DR5 levels through ROS generation and the CHOP pathway.